Anxiety and depression of Ukrainian school-age children in the process of distance education during the СOVID-19 pandemic - Hozak, Svitlana; Yelizarova, Olena; Stankevych, Tetiana; Дюба, Наталія; Parats, Alla; Lebedynets, Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The introduction of distance education (DE) challenged all participants in the educational process and it was impacting the well-being of children. The purpose of the study was investigating the impact of different forms of DE on values of anxiety and depression (A&D) in school-age children. Methods. An online survey of 760 respondents was conducted with use RCADS. All respondents signed informed consent. ANOVA was used for statistical analysis (STATISTICA 8.0). The models were adjusted for age and gender of respondents. Results. More than 20% of parents have reported their own and their children’s high psychological stress during DE. The adaptation was easier and faster for respondents who were able to organize a virtual communication and got support from teachers. Pathological increase of the level A&D has been detected in 14.4±1.3% of respondents. There were 2.8 times more girls with clinical A&D than boys (p<0.001). The DE formats of "All-Ukrainian online school" and individual learning did not significantly affect the level of A&D in school-age children (p>0.5). DE in the form of tasks in messengers and social networks significantly increased the level A&D (p<0.001), and DE offline increased only the level of Anxiety (p<0.05). Reductions the level A&D have been identified in online lessons with the teacher and the schoolfellows (p<0.001). The chances of increasing the level of anxiety and depression in school-age children grow in 1.8 times when using non-interactive forms of education (OR=1.78; CI 1.17-2.69; p<0.01). Conclusions. Teacher support and online lessons help reduce psychological discomfort during distance education. The surveillance the mental health of children is required during the implementation of various forms of DE.